FRI0456 Age at spondyloarthritis diagnosis and risk of cardiovascular comorbidity: results from the comospa study. (15th June 2017) - Derakhshan, MH; Goodson, NJ; Packham, J; Sengupta, R; Marzo-Ortega, H; Molto, A; Siebert, S; ,
Abstract : Background: Spondyloarthritis (SpA) and chronic inflammatory diseases are associated with a number of cardiovascular comorbidities. It is unknown whether age at SpA diagnosis is associated with cardiovascular outcomes in later life. Objectives: To examine the relationship between "younger age at SpA diagnosis" and risk of various cardiovascular comorbidities. Methods: COMOSPA is a large worldwide cross-sectional study comprising 3984 patients from 23 countries evaluating comorbidities in patients with SpA (1). We evaluated the association between "younger age at SpA diagnosis" (defined in 5-year blocks) and cardiovascular comorbidities using uni-variable and multi-variable binary logistic regression. Each model comprised one cardiovascular co-morbidity as dependent and "age at SpA diagnosis" as predictor adjusted for age, sex, BMI, history of smoking, alcohol, NSAIDs, DMARDs, biologics, steroids and other relevant factors Results: The data of 3923 patients (64% male) were available for analysis. Current age ranged from 18 to 100 with median (IQR) of 42 (32–53) years. The median (IQR) age at SpA diagnosis was 33 (25–43) years. Main reported cardiovascular-related comorbidities were hypertension (22.4%), ischemic heart disease (IHD) (2.6%), stroke (1.3%) and diabetes mellitus (5.5%). The risk of hypertension, after adjustment for potential confounding factors was associated with younger age at SpA diagnosis (OR=1.10, 95% CI: 1.05 -1.16), indicating 10% higher risk of hypertension for each 5 year younger age at time of SpA diagnosis (Table). Confounding variables showing significant association with hypertension were current age (OR=1.12, 95% CI: 1.10–1.13, p <0.001), male gender (OR=1.47, 95% CI: 1.20–1.80, p <0.001), current BMI (OR=1.09, 95% CI: 1.07–1.11, p <0.001), ever use of steroids (OR=1.24, 95% CI: 1.03–1.50, p =0.027) and ever use of synthetic DMARDs (OR=1.28, 95% CI: 1.05–1.57, p =0.017), but not ever use of NSAIDs or biologic DMARDs. The other cardiovascular comorbidities were not associated with "younger age at SpA diagnosis" after adjustments for relevant confounding factors in multivariable analyses (Table) Conclusions: Younger age of SpA diagnosis is associated with increased risk of developing hypertension but not other cardiovascular comorbidities in this study. The explanation for this association is not clear and does not appear to be due to increased NSAID exposure. References: Molto A, et al. Ann Rheum Dis 2016;75:1016–23. Disclosure of Interest: None declared